KEBUTUHAN MATERIAL PENYEMENAN DALAM PENYEMENAN CASING LINER TUJUH INCH SUMUR X-13 LAPANGAN Y - Hastowo Resesiyanto (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
Cementing is a process of mixing cement powder, water and additives (cement slurry) which will be pumped into the wellbore through casing into the annulus along the wellbore. Liner is a casing hung onto the casing which has been set before. Before the calculation of cementing materials needed, it is needed to collect X-13 well data, in the form of well profile which is consist of casing and tubing dimension. Furthermore, laboratory data for cement and additives is also used. Based on the calculation, the total volume of cement slurry needed for open end interval cementing is 199.7 bbl, with the amount of cement sack needed is 595.2 sacks. The total solid additives needed is 21426.1 lbs and total liquid additives needed is 1294.542 gallons. The total volume of fluid needed to push the cement slurry into the cementing zone is 251.05 bbl.